PENGEMBANGAN MODUL LIMBAH CAIR TAPIOKA SEBAGAI SUMBERBELAJAR PADA SUBMATERI LIMBAH DI SMA N 1 JAKENAN - Khasanah, Uswatun; Bintari, Siti Harnina; Iswari, Retno Sri (Journal of Biology Education, 2014)
Tapioca liquid waste was discharge into the river without prior treatment caused pollution. Meanwhile polluted environment can be used as a learning resource. Learning resources in Jakenan senior high school only worksheet and material book that not all students have them, made teacher centered learning impact. The research aim to determine the eligibility of modules tapioca liquid waste as learning resources on subchapter waste and to determine modules application on learning outcome. The research design applied in this research is a Research and Development (R&D). The research has been conducted in first semester 2013/2014 in Jakenan senior high school. The subject of research was the students. The Product usage test samples taken by convenience sampling method. The expert judgment result of modules was developedÂ  reached 91 %, student responses reached 94 %, teacher responded that the modules very feasible to used as learning resources and all students (100%) has reached the minimum mastery criteria set (72). Based on the results of the research modules eligible as learning resources.Limbah cair tapioka yang dialirkan ke sungai tanpa pengolahan terlebih dahulu mengakibatkan pencemaran. Lingkungan yang tercemar dapat dimanfaatkan sebagai sumber belajar. Sumber belajar di SMA N 1 Jakenan hanya berupa LKS dan buku paket yang tidak semua siswa memiliki, menyebabkan pembelajaran berpusat pada guru. Penelitian ini bertujuan untuk mengetahui kelayakan modul limbah cair tapioka sebagai sumber belajar pada submateri limbah dan untuk mengetahui penerapan modul terhadap hasil belajar. Desain yang diterapkan dalam penelitian ini adalah penelitian dan pengembangan (Research and Development). Penelitian dilakukan pada Semester Gasal tahun ajaran 2013/2014 di SMA N 1 Jakenan. Sampel uji coba pemakaian produk diambil dengan metode convenience sampling. Hasil penilaian pakar terhadap modul yang dikembangkan 91 %, tanggapan siswa mencapai 94 %, guru menanggapi bahwa modul tersebut sangat layak digunakan sebagai sumber belajar dan semua siswa (100%) telah mencapai Kriteria Ketuntasan Minimal yang ditetapkan (72). Berdasarkan hasil penelitian modul yang dikembangkan layak dan digunakan sebagai sumber belajar.